MODEL DESAIN UNIT PELAYANAN KEBIDANAN YANG BERPUSAT PADA KELUARGA (FAMILY-CENTERED CARE) - Astri Ulina Saragih; Enrika T. Pasaribu; Septa Hayati Harahap (Politeknik Ganesha Medan, 2023)
Traditional midwifery care often focuses on a biomedical approach to mother and baby, but current global trends are moving toward a more holistic and inclusive care model. The Family-Centered Care (FCC) approach to midwifery care recognizes the family as a fundamental unit that needs to be actively involved in every aspect of care. This literature review examines the principles of FCC, the key components of an FCC-based midwifery care unit design model, and the benefits and challenges of its implementation. The goal is to provide guidance for practitioners, health facility managers, and policymakers in designing a midwifery care environment that supports family involvement and enhances positive experiences for all family members.